Barriers to access: availability and affordability of essential drugs in a retail outlet of a public health center in south western Ethiopia - Zelalem Abiye, Amene Tesfaye, Segewkal Hawaze (Journal of Applied Pharmaceutical Science, 2013)
Essential drugs (EDs) satisfy the priority health care needs of a population and their availability and affordability at all times is crucial for provision of complete health service. The study aimed to assess availability and affordability of treatment cost for common diseases in Jimma Health Center (JHC). A cross sectional study was conducted using structured data abstraction form for exit interviews and checklists. Only 128 (55.65%) EDs were available. The average price for commonly used drugs per recommended dose for an individual patient in JHC Pharmacy, Ethiopian Red Cross (ERC) Pharmacy and Private Pharmacies were $0.65, $0.62 and $0.94 respectively. Affordability of medications was significantly associated with age, marital status, occupational status, gross monthly income and number of economically dependent family members (p
Keywords: Average Price, Informal Sector, Private Pharmacies and Jimma.